SLEEP QUALITY, FATIGUE AND SLEEPINESS IN MEDICAL STUDENTS - Baljak, Anja; Nikolic, Aleksandra; Grujicic, Sandra (HEALTH CARE, 2023)
Introduction/Aim: Medical students are exposed to a significant level of pressure due to academic demands, resulting in decreased sleep quality, fatigue, and increased daytime sleepiness, all of which can affect learning efficiency, academic success, and motivation. The research aimed to examine the prevalence of fatigue, sleep quality and daytime sleepiness among medical students and their interrelationship. Methods: The study was conducted as a cross-sectional study in December 2022 among 316 third-year students of the Faculty of Medicine, University of Belgrade. The data were collected by a survey questionnaire, which students filled out at the beginning of practical classes in the subject of Epidemiology. In addition to demographic data, students filled out a questionnaire on sleep quality (Pittsburgh Sleep Quality Index-PSQI), a questionnaire on fatigue (Fatigue Severity Scale-FSS), and a sleepiness scale (Epworth Sleepiness Scale-ESS). Descriptive statistics, χ2 test, and Student’s t-test were used in the statistical analysis of the data. p < 0.05 was used as a statistically significant value. Results: The study included 312 third-year students of the Faculty of Medicine of the University of Belgrade, 86 men (27.5%) and 226 women (72.2%). The average age of the students was 21.37 years. More than half of the students (54.7%) had poor sleep quality, every fourth student had increased fatigue (27.6%), and almost half of the students had increased levels of sleepiness (45.8% ). There was no significant difference between men and women in sleep quality and level of fatigue, but women significantly more often had higher levels of daytime sleepiness (p=0.008). Male students who had increased fatigue significantly more often had poorer sleep quality than students with normal fatigue levels. While female students with an elevated level of fatigue significantly more often had poorer sleep quality and increased daytime sleepiness. Conclusion: Poor sleep quality, fatigue, and sleepiness were common in the population of medical students. More than half of the students (54.7%) had poor sleep quality, every fourth student had increased fatigue (27.6%), and almost half of the students had increased levels of sleepiness (45.8%). Therefore, it is necessary to encourage medical students to have a healthier lifestyle and adequate sleep patterns even in the earlier years of their studies.